ASSOCIATION OF BODY COMPOSITION AND BIOCHEMICAL INDICATORS WITH THE PREVALENCE OF COMMON CARDIOVASCULAR DISEASES AMONG COMMUNITY-DWELLING OLDER ADULTS, 2021–2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To analyze the association between body composition, selected biochemical indicators, and the presence of common cardiovascular diseases among community-dwelling older adults during 2021-2025.Methods: A cross-sectional descriptive study with analytical components was conducted among 6,203 older adults from eight provinces/cities in Vietnam. The dependent outcome was the presence of at least one common cardiovascular disease identified through community screening, paraclinical results, and available health records. Associations between body composition indices, selected biochemical markers, and cardiovascular diseases were assessed using univariable and multivariable logistic regression.Results: No significant association was found between body mass index (BMI), waist-to-hip ratio, and cardiovascular diseases among older adults. However, several blood biochemical indicators, including total cholesterol, high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C), were associated with the prevalence of common cardiovascular diseases in the elderly. An increase of 1 mmol/L in total cholesterol and LDL-C was associated with a 4.07-fold and 3.35-fold higher risk of cardiovascular diseases, respectively. Elevated blood glucose was identified as a potential related factor.Conclusion: In the current model, BMI and waist-to-hip ratio were not statistically associated with common cardiovascular diseases among older adults. Three biochemical indicators associated with disease status were total cholesterol and LDL-C.
Keywords: associated factors; cardiovascular diseases; older adults.